Employment and Empowerment: Assessing Changing Status of Dalit Women in Chadani Village, Mahakali Municipality (Research Nepal Journal of Development Studies, 2024)
Employment is recognized as a critical pathway for women's empowerment, yet its potential is often circumscribed by systemic barriers. This is particularly true for Dalit women in Nepal, who face the compounded burdens of gender and caste-based discrimination. This study investigates the nexus between economic participation and the empowerment of Dalit women, using a case study of Chadani Village in Mahakali Municipality. Based on a mixed-methods approach, data were collected from 50 households (25 employed and 25 unemployed Dalit women) through structured questionnaires. The findings reveal that despite a progressive national policy framework, a significant implementation gap persists. Deep-rooted discriminatory practices, illiteracy, and hierarchical cultural norms continue to limit access to health, education, and formal economic opportunities. However, the study demonstrates a clear correlation between employment and enhanced status. Employed women, especially those in government service, exhibited greater confidence, decision-making autonomy within the household, and higher social participation compared to their unemployed counterparts. The research concludes that while economic independence is a crucial catalyst for empowerment, it must be supported by a multi-faceted approach. Effective implementation of existing policies, community-based awareness campaigns, legal reforms to abolish discriminatory practices, and initiatives promoting shared domestic responsibilities are essential. Ultimately, transformative change requires empowering Dalit women economically, socially, and politically to overcome entrenched marginalization.